The International Finance Corporation's MBA Survey : How Developing Country Firms Rate Local Business School Training - Chaudhry, Azam (World Bank, Washington, DC, 2014)
Graduate education in business administration was developed in the U.S. around the turn of the twentieth century. MBA and similar graduate-level business programs took hold more slowly in other countries, but the number of such programs expanded more rapidly from the 1960s onward. In an effort to determine what firms from these countries require from business school graduates, the IFC used its extensive contacts with these firms to conduct a survey of the quality of business education in these countries. The survey results imply that the strengths and weaknesses of developing and transition country MBAs seem to overlap with those of MBAs from the U.S.: managers in the U.S. and in the developing countries find that the technical and analytical skills of MBAs are well developed while the practical training/skills and communication/language skills of MBAs are significantly lacking. On the whole, only the African and Middle Eastern firms were significantly dissatisfied with the quality of local MBA graduates. The survey results show that MBAs worldwide are not fully satisfying the needs of firms. Each of the other regions of the world has its own particular weaknesses, while at the same time some common weaknesses (such as work experience and communication skills) stand out. These results show that a cookie-cutter approach to training MBAs cannot work. Rather, MBA programs have to be tailored to suit the needs of the local business community while also teaching common business fundamentals.